Στρατηγικές Ναυτιλιακών Επιχειρήσεων σε Περιόδους Ύφεσης - Κύρου, Κωνσταντίνος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών, 2017)
Ship management evolved from an in-house function of the ship owners to a formal organisation to manage their vessels, performing the most basic functions of crewing, technical management, supply and compliance with statutory matters and industry best practices. Strategy followed by a shipping company in turbulent times is a key factor for gaining competitive advantage, improving its position against competitors and in general increasing its profits. The research problem of this study is to investigate the strategies followed by shipping companies in turbulent times and practices used to maintain their good performance. Therefore, the aim of this research is to review the existing business strategies and practices during turbulent times and identify those resulting in improving performance of shipping companies. The existing experience is based on the literature and the shipping executives’ perceptions on current strategies. More specifically, at a first stage, the work analyzes the shipping business environment and identifies strategies followed by shipping companies. Strategic anticipation is considered as part of business strategy in an unpredictable and potentially volatile environment, following brief description of best practices, such as flexible planning and resilience development. Then, at a second stage, the work identifies the most appropriate strategies and practices followed by shipping companies in turbulent times. Except for the existing literature, the experience is presented through statistical processing of questionnaires as well, which have been distributed to a representative sample of executives. Finally, at a later stage, the work discusses the results and draws final conclusions. The main result received through this research is that the main competitive strategies followed in turbulent times are cost leadership and differentiation. The quality and the cost of services are the most important benefits of shipping companies, which introduce technology innovations and implement best practices in Crew, Safety & Quality, Technical, Supplies and Financial management, giving them flexibility to adapt strategy and operations. The “winners” likely will be those companies that truly manage to “navigate” the changing ship business environment. A winning strategy might be the one that embraces a new sense of responsibility, better collaboration with all stakeholders involved, including partners, suppliers, vendors, and customers; assert sustainability as part of business strategy; enable effective management of sustainability impacts across and between value chains with civil society organizations, customers and regulators - to enable innovative solutions to be realized.